MENINGKATKAN KUALITAS PROSES BELAJAR SISWA MELALULI STRATEGI PEMBELAJARAN KREATIF PRODUKTIF PADA MATERI KLASIFIKASI MAKHLUK HIDUP DAN TAK HIDUP - Bambang Suprayogi (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2016)
ABSTRACTSelection of teaching methods largely determine the quality of teaching in the learning process. To enhance the students 'learning process necessary to activate learning strategy, challenge and empower students' thinking skills to find the concept itself, so it can help students gain a deeper understanding and meaningful. One of the learning strategies that can membelajarkan students are learning strategy kreaktif productive. Strategy pembelajran Airport has 5 syntax, namely: the orientation phase, the exploration, interpretation stage, the stage of re-creation, and evaluation phase. Based on observations during the learning process it was found that the activity of students during the learning process has increased. This was evident during the learning process seen active interaction between students and students, students and teachers, and the interaction between students with learning media used. It shows that during the learning process has been an increase in motivation, enthusiasm for learning and curiosity of students, the courage of students in the opinion, and cooperation among students in learning, as well as the responsibility of the student in completing the task group. This means the quality of student learning has improved. This increase can be realized thanks to the motivation and guidance teacher for learning, good cooperation between students and teachers, as well as the emergence of intrinsic motivation and awareness of students to learn. KEYWORDS: creative productive learning strategies, learning students